Analisis Sintaksis: Fungsi, Kategori, dan Peran Pada Berita Detik.com - Septiani, Alika Dwi; Maheltra, Alma Neysa; Heryanti, Denia; Adawiyah, Sulis Najahul; Suherman, Syahira Mawla; Lisnawati, Iis (Innovative: Journal Of Social Science Research, 2025)
Language as the main communication tool has a complex structure, one of which can be studied through syntax, namely the study of word order in forming sentences. This study aims to describe the sentence structure, function, category, and role of syntax in the Detik.com news text entitled "Rejection of the TNI Law Continues to Roll Through Tents at the DPR Building". By using a qualitative descriptive method with discourse analysis techniques, this study identified the syntactic structure of the sentences in the news text. The results of the study show that the sentences in this news text generally have structures such as S-P, S-P-O, S-P-O-Pel, S-P-K, S-P-Pel, S-P-O-K, and S-P-O-Pel-K. The most dominant syntactic elements used are the subject as the actor and the predicate as the action. The grammatical categories that are often found include nominal phrases as subjects or objects, and verbal phrases as predicates. This study shows how syntactic elements interact with each other in forming effective and communicative sentences in the context of mass media discourse.